Implementasi Project Based Learning sebagai Upaya Pengembangan Sikap Ecopreneurship pada Mata Kuliah Manajemen Lingkungan - Novita Ekasari; Novita Sari; Ade Perdana Siregar; Garry Yuesa Rosyid (Universitas Batanghari Jambi, 2023)
Human resources are the main actors in regional economic development, so readiness is needed in creating quality human resources. Education graduates in fulfilling the need for social services and employment are still often a burden on the government, the factors causing the lack of skills in students are the lack of meaning and not yet contextual in learning patterns so that the value of life includes independence, innovation, creativity and life skills start to disappear. The purpose of this research is to examine the effect of applying the project based learning model with the case method in developing ecopreneurship attitudes among students teaching environmental management courses. The research method as an evaluation stage used in this research is descriptive research method. The analysis used is qualitative analysis by collecting data from the results of in-depth interviews and observations of students who teach environmental management courses. The results of the research are that the project based learning model in environmental management courses using the case method can improve ecopreneurship attitudes in students, environmental management problems and solutions, business people and academics are required to be able to foster an ecopreneurship attitude in order to be able to innovate to provide solutions to environmental problems